2002
DOI: 10.1103/physrevb.66.094401
|View full text |Cite
|
Sign up to set email alerts
|

Long-time tails and anomalous slowing down in the relaxation of spatially inhomogeneous excitations in quantum spin chains

Abstract: Exact analytic calculations in spin-1/2 XY chains show the presence of long-time tails in the asymptotic dynamics of spatially inhomogeneous excitations. The decay of inhomogeneities for t→ϱ, is given in the form of a power law (t/ Q ) Ϫ Q , where the relaxation time Q and the exponent Q depend on the wave vector Q, characterizing the spatial modulation of the initial excitation. We consider several variants of the XY model ͑dimerized, with staggered magnetic field, with bond alternation, and with isotropic an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
16

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 60 publications
1
14
0
16
Order By: Relevance
“…The relaxation from a large class of initial conditions was considered in numerous studies starting from late sixties; see [32,33,34,35] and [36] for a review of more recent work. Our focus, however, is on non-equilibrium states with a non-vanishing current.…”
Section: Modelmentioning
confidence: 99%
“…The relaxation from a large class of initial conditions was considered in numerous studies starting from late sixties; see [32,33,34,35] and [36] for a review of more recent work. Our focus, however, is on non-equilibrium states with a non-vanishing current.…”
Section: Modelmentioning
confidence: 99%
“…Consequently, in such systems there is no finite relaxation time. Moreover, it was shown that for certain inhomogeneously magnetised initial states, at special wave vectors, a slowing down of the magnetisation relaxation can occur for gapped free fermionic models ‡ Corresponding author: karevski@lpm.u-nancy.fr [9]. The effect of quenched disorder was also considered in the Ising quantum chain [27].…”
Section: Introductionmentioning
confidence: 99%
“…as a linear combination of independent particular solutions r n and r −n . In (12) and subsequent relations, the index λ is omitted. Substitution in relation (11) leads to the spectrum:…”
Section: Model Calculationmentioning
confidence: 99%